Analisis Pengetahuan Generasi Milenial Non Muslim Terhadap Bank Syariah di Kota Solo - Rizka Awaliya Nur Azizah; Agung Abdullah (Fakultas Ekonomi dan Bisnis Islam UIN STS Jambi, 2023)
This study aims to determine the knowledge level of non-Muslim millennial generation towards Islamic banks in Solo City. This type of research uses a qualitative methode with the Accidental Sampling technique by interviews with 8 non-Muslim millennial generation respondents. The results of this study, for the first category of knowledge about the existence of Islamic banks, 88% non-Muslim millennial generation knows about the existence of Islamic banks. The second and third category is about operations and the product of Islamic bank has same result above 63 % of non-Muslim millennial generation does not know the operations products and services provided by Islamic banks of Islamic banks. The fourth category about the differences between conventional banks and Islamic banks, only 50% of the non-Muslim millennial generation know about it. The existence of Islamic banks that are universal is not generally known by the non-Muslim millennial generation even its in a big City. Non-Muslim millennials think that knowledge of Islamic banks is only limited to sharia labels without knowing about the operations, products and services of Islamic banks.